PENGARUH PENGGUNAAN MEDIA SPARKOL VIDEOSCRIBE TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI RUPA DI SMP NEGERI 4 PADANG - PUTRI DWI SURYANI, Dra. Zubaidah, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2018)
This study was aimed to find out if there was any significant differences between students’ learning outcomes using Sparkol Videoscribe learning media and students learning outcomes without Sparkol Videoscribe in fine art study at SMP N 4 Padang . Type of research used was quantitative research with quasi experiment (Quasi Eksperimen), population used in this study was all of the students of SMP N 4 Padang with the sample was purposive random sampling. Based on the data processing, it can be concluded that there was a differences between students learning outcomes using Sparkol Videoscribe learning media and students learning outcomes without Sparkol Videoscribe with 0,000<0,05 significant level. The conclusion is that the use of Sparkol Videoscribe media has an effect on learning outcomes in fine art study at SMP N 4 Padang.